Novel substrate specificities of two lacto-N-biosidases towards β-linked galacto-N-biose-containing oligosaccharides of globo H, Gb5, and GA1. (18th May 2015) - Gotoh, Aina; Katoh, Toshihiko; Sugiyama, Yuta; Kurihara, Shin; Honda, Yuji; Sakurama, Haruko; Kambe, Taiho; Ashida, Hisashi; Kitaoka, Motomitsu; Yamamoto, Kenji; Katayama, Takane
Abstract: We describe the novel substrate specificities of two independently evolved lacto-N-biosidases (LnbX and LnbB) towards the sugar chains of globo- and ganglio-series glycosphingolipids. LnbX, a non-classified member of the glycoside hydrolase family, isolated from Bifidobacterium longum subsp. longum, was shown to liberate galacto-N-biose (GNB: Galβ1-3GalNAc) and 2′-fucosyl GNB (a type-4 trisaccharide) from Gb5 pentasaccharide and globo H hexasaccharide, respectively. LnbB, a member of the glycoside hydrolase family 20 isolated from Bifidobacterium bifidum, was shown to release GNB from Gb5 and GA1 oligosaccharides. This is the first report describing enzymatic release of β-linked GNB from natural substrates. These unique activities may play a role in modulating the microbial composition in the gut ecosystem, and may serve as new tools for elucidating the functions of sugar chains of glycosphingolipids. Graphical abstract: Highlights: Gut microbes have evolved selected enzymes to degrade host-derived glycans. We reveal novel substrate specificities of two non-homologous lacto-N-biosidases. LnbX, a non-classified GH member, acts on Gb5 and globo H oligosaccharides. LnbB, a member of GH20, acts on GA1 and Gb5 oligosaccharides. These enzymes will provide new tools for glycobiology.